Comunicación interpersonal y vida cotidiana. La presentacion de la identidad de los jóvenes en Internet - Cáceres, María Dolores; Ruiz San Román, José A.; Brändle, Gaspar (CIC. Cuadernos de Información y Comunicación, 2009)
The goal of this paper is to show some features about how the young people appear themselves before others through the processes of interpersonal communication with technological mediation. Firstly, we focus on the transformations operated by the technological mediation in the processes of interpersonal communication; secondly, emerges the question of the identity and the anonymity in the network, which are the Internet implication in terms of genuineness and how that identity is experienced and played by relation to some scenes of the everyday life. This exploratory study results from an online questionnaire completed for 360 university young men and women Internet users, in 2008. Le but de cet article est de montrer quelques traits de la présentation des jeunes gens devant eux-mêmes à travers les procès de la communication interpersonnelle avec le concours de la médiation technologique. En premier lieu on aborde les transformations subies dans la médiation du procès de la communication interpersonnelle; après, la question de l’identité et de l’anonymité dans la web, et son implication autour de la nature génuine de l’ Internet, et comment s’ experiment l’ identité, comment elle se joue dans sa relation avec les scenes de la vie quotidienne. Cet étude exploratoire est le résultat d’un questionnaire on line developpé entre 360 jeunes universitaires, filles et garçons, en 2008.